INTERNALIZATION OF MORAL VALUES THROUGH THE SHILATURRAHIM TRADITION IN THE YOUTH MOVEMENT RIYADLUL JANNAH MADURA AND SYUBBAN LOVERS PAMEKASAN - Rohman, Mujibur; Maski, Maski (LP2M IAI Al-Khairat Pamekasan, 2024)
This study aims to analyze the process of internalizing moral values through the shilaturrahim tradition practiced by the Riyadlul Jannah Youth Movement in Madura and the Syubban Lovers in Pamekasan. The research focuses on how social and religious activities within these organizations shape the moral character of the younger generation. The research method used is qualitative with a case study approach, where data were collected through participant observation, in-depth interviews, and documentation of organizational activities. The informants consisted of members and leaders actively involved in the shilaturrahim activities. Data analysis was conducted using thematic analysis techniques to identify patterns and themes related to the internalization of moral values. The findings indicate that the shilaturrahim tradition serves as an effective medium for internalizing values such as respect, compassion, solidarity, and social care. These values are internalized through a gradual process involving knowledge, acceptance, and application in everyday life. Routine activities such as monthly gatherings and annual programs provide a space for members to experience and internalize these values, making them part of the members' moral identity. This study concludes that the shilaturrahim tradition significantly contributes to the character formation and moral development of the younger generation through active and dialogic social interactions.